Subacute parkinsonism induced by immune checkpoint inhibitors - Lénia Silva; Inês Laranjinha; Cláudia Casais; Raquel Samões (Annals of Movement Disorders)
Immune checkpoint inhibitors can trigger immune-related side effects, and while neurological involvement is rare, it can be serious. A woman with treatment-refractory intestinal T-cell lymphoma was initiated pembrolizumab and developed a daily fever and parkinsonian syndrome 2 weeks later. The investigation revealed only mild slowing of the background activity on electroencephalogram and slightly elevated cell count and protein levels in her cerebrospinal fluid. Immunotherapy was discontinued, and the patient recovered after 5 days of methylprednisolone. Minor neurological symptoms recurred after the rechallenge with pembrolizumab. Subacute parkinsonian syndromes should be considered a potential neurological event related to immune checkpoint inhibitors.